Outcome of pars plana vitrectomy versus scleral buckling in the treatment of rhegmatogenous retinal detachment - Saifulla-Hel-Azam, M.; Nabil, Abrar Ahmed; Das, Goutam; Muhammad Sayem, Sha; Najnin, Mosfica; Sultana, Nahid (International Journal of Research in Medical Sciences, 2024)
Background: Variety of surgical techniques are available to treat RRD. So, it is very difficult to choose the option. Objectives were to assess and compare the surgical outcome which includes retinal re-attachment rate, functional success rate and post-operative complications between pars plana vitrectomy (PPV) and scleral buckling (SB) in the treatment of rhegmatogenous retinal detachment (RRD). Methods: This prospective observational study was conducted on 60 (sixty) eyes of 60 (sixty) patients with RRD in vitreo-retina department, at NIO and H. Subjects were divided into SB group (n=30) and PPV group (n=30). Ophthalmological data were included pre-operative and post-operative visual acuity, refractive status of the eye, intra ocular pressure, presence and extent of RRD, number and location of retinal breaks, presence of proliferative vitreoretinopathy, status of macula and peripheral retinal degenerations. Results: Among 60 patients, majority (30% and 36.7%) were in the age between 41-50 years in PPV and SB group respectively. In both groups, males were predominant. Majority breaks were in total 25 (41.7%) eyes in superotemporal quadrant. Subtotal RRD was highest, in 19 (31.7%) eyes in total. Retinal anatomical re-attachment was achieved in total 55 (91.7%) eyes; among them 27 (90.0%) eyes in PPV group and 28 (93.3%) eyes in SB group. Conclusions: Scleral buckling surgery may be taken as a unique option for uncomplicated rhegmatogenous retinal detachment surgery, as it is non-invasive and not accompanies with high incidence of post-operative cataract formation.